1978
DOI: 10.1084/jem.147.4.997
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive factors from lymphoid cells of nonresponder mice primed with L-glutamic acid60-L-alanine30-L-tyrosine10. IV. Lack of strain restrictions among allogeneic, nonresponder donors and recipients.

Abstract: The synthetic terpolymer of L-glutamic acid60-L-alanine30-L-tyrosine10 (GAT) fails to stimulate development of GAT-specific antibody responses in nonresponder mice but stimulates development of GAT-specific suppressor T cells that inhibit the development of normal anti-GAT plaque-forming cell responses to GAT complexed to methylated bovine serum albumin (MBSA). Extracts from lymphoid cells of GAT-primed but not control, nonresponder (DBA/1) mice contain a T-cell factor (GAT-TsF) that also specifically suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

1980
1980
1984
1984

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…The amplification in the TsF-mediated suppres sion involving Lyt-l+,2+,3+ T cells has also been dem onstrated by Waltenbaugh et al [7], Kapp [8] and Ger main et al [9,10,20] in the suppression of the primary antibody formation against synthetic polypeptides. They demonstrated that the administration of a TsF which derives from Lyt-1 idiotypic T cells (Tsl) acts on the anti-idiotypic suppressor precursor cell of Lytl+,2+,3+ phenotype to induce the effector type Lyt-2+,3+ Ts2 [20].…”
Section: Discussionmentioning
confidence: 93%
“…The amplification in the TsF-mediated suppres sion involving Lyt-l+,2+,3+ T cells has also been dem onstrated by Waltenbaugh et al [7], Kapp [8] and Ger main et al [9,10,20] in the suppression of the primary antibody formation against synthetic polypeptides. They demonstrated that the administration of a TsF which derives from Lyt-1 idiotypic T cells (Tsl) acts on the anti-idiotypic suppressor precursor cell of Lytl+,2+,3+ phenotype to induce the effector type Lyt-2+,3+ Ts2 [20].…”
Section: Discussionmentioning
confidence: 93%
“…3600 Immunology: Wieder et aL Affinity Chromatography. Sepharose-immobilized mouse anti-I9 and anti-I-J8 antisera were prepared by coupling heatinactivated alloantisera by cyanogen bromide-activated Sepharose 4B as described (10). In vitro translated material (30 1ul) was incubated with 50 Al of Sepharose-conjugated anti-P9 or anti-I-J' antisera for 2 hr at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The mechanism(s) by which GAT-specific suppressor T cells regulate immunity has been investigated by analysis of T cell extracts from GAT-primed nonresponder mice (8)(9)(10). These extracts contain a specific factor, GAT-T cell suppressor factor (GAT-TsF), that inhibits plaque-forming cell (PFC) responses to GAT-methylated albumin in vivo and in vitro and also inhibits T cell proliferative responses in nonresponder mice primed with GAT-methylated albumin (11).…”
mentioning
confidence: 99%
“…Affinity-purified GAT-TsF is a protein of estimated Mr 45,000-60,000 determined by gel filtration and has the ability to bind specifically to GAT (9). The antigen-binding moiety bears determinants that appear to be encoded both by the Ig variable heavy chain gene complex and the I-J subregion of the major histocompatibility gene complex (10,11). …”
mentioning
confidence: 99%
“…The insoluble complex, GAT-methylated albumin, was prepared as described (3). DBA/1 or B10.Q mice were injected in the hind foot pad with [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] ,g of GAT as GAT-methylated albumin emulsified in complete Freund's adjuvant containing Mycobacterium tuberculosis H37 Ra (8).…”
mentioning
confidence: 99%